Laparoscopic Ovarian Drilling Improves Endometrial Homeobox Gene Expression in PCOS - Senturk, Senol; Celik, Onder; Dalkilic, Semih; Hatirnaz, Safak; Celik, Nilufer; Unlu, Cihat; Otlu, Baris (Springer Heidelberg, 2020)
The study was designed to investigate whether laparoscopic ovarian drilling (LOD) of ovaries alters the expression levels of HOXA-10 and HOXA-11 mRNA in the endometrium of infertile women with clomiphene-resistant PCOS. Expression of HOXA-10 and HOXA-11 mRNA in the endometrium obtained before and after LOD during the midsecretory phase was measured. Expression of each gene was evaluated using real-time reverse transcriptase polymerase chain reaction (RT-PCR). Expression levels of HOXA-10 and HOXA-11 mRNA were lower in endometrium of patients with PCOS before LOD compared with fertile controls. But the differences failed to show statistical significance. Compared with fertile subjects, LOD of PCOS ovaries up-regulated endometrial HOXA-10 and HOXA-11 mRNA expression. Fold changes of HOXA-10 and HOXA-11 mRNA after LOD were found to be 4.46 and 4.19, respectively. Fold change increase in HOXA-10 and HOXA-11 mRNA was found to be statistically significant (P < .01, P < .02). There is a receptivity defect in the endometrium of women with PCOS that affects fertility regardless of other causes of infertility. LOD increases endometrial HOXA-10 and HOXA-11 mRNA expressions and improves receptivity in patients with clomiphene-resistant PCOS.
Keywords: PCOS; Ovarian drilling; HOXA gene; Receptivity